Fast and sensitive LC-MS/MS method for the simultaneous determination of lisinopril and hydrochlorothiazide in human plasma - Jaivik V. Shah; Priyanka A. Shah; Priya V. Shah; Mallika Sanyal; Pranav S. Shrivastav (Elsevier, 2017)
A sensitive and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) method has been developed for the simultaneous determination of lisinopril (LIS) and hydrochlorothiazide (HCTZ) in human plasma using their labeled internal standards (ISs). Sample pre-treatment involved solid phase extraction on Waters Oasis HLB cartridges using 100 µL of plasma, followed by liquid chromatography on Hypersil Gold C18 (50 mm×3.0 mm, 5 µm) column. The analytes were eluted within 2.0 min using acetonitrile-5.0 mM ammonium formate, pH 4.5 (85:15, v/v) as the mobile phase. The analytes and ISs were analyzed in the negative ionization mode and quantified using multiple reaction monitoring. The method showed excellent linearity over the concentration range of 0.50-250.0 ng/mL for both the analytes. The intra-batch and inter-batch precision (% CV) was ≤5.26% and their extraction recoveries were in the range of 96.6%-103.1%. Matrix effect evaluated in terms of IS-normalized matrix factors ranged from 0.97 to 1.03 for both the analytes. The validated method was successfully applied to determine the plasma concentration of the drugs using 10 mg lisinopril and 12.5 mg hydrochlorothiazide fixed dose formulation in 18 healthy Indian volunteers.